Lichen striatus in a 6-month-old baby girl. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2018)
Lichen striatus (LS) is a linear papular dermatitis that occurs between the ages of 5 and 15, mostly asymptomatic and self-healing in months, usually unilateral (1) and non-recurrent. It is often followed by hypomelanic outcomes that may persist for years. LS is characteristically distributed along the lines of Blaschko leading to suggest a nevus condition due to a post-zygotic mutation that gives rise to a clone of mutated cells; the mutation consists in a functional and not morphological alteration that becomes evident when the organism encounters a triggering factor, to which only the mutated cells react with consequent inflammation. The current case is an expression of the individual variability of the Blaschko lines (Fig. 2, courtesy of prof. Rudolph Happle, reference n. 2) because it had a straight downward course and did not describe an upward concave curve to join the tragus to the labial commissure (2).